Export emergence of differentiated goods from developing countries: export pioneers and business practices in Argentina - Artopoulos, Alejandro Martín (2013)
This study explores the underlying factors that enable firms from developing countries to successfully export differentiated goods to developed countries. The article describes four case studies of export emergence in differentiated-good sectors in Argentina, namely wine, television programs, motorboats, and wooden furniture. The case studies rely primarily on an extensive set of interviews. We find that consistent exporters to developed countries adopt a newset of business practices that differ starkly fromthose that prevail in their domestic market. In three of the sectors, an export pioneer led the adoption of these new practices. Export pioneers possessed tacit knowledge about foreign markets, achieved through their previous embeddedness in the business community of those markets. Export emergence occurs as business practices diffuse throughout the sector. These findings point to the importance of foreign market knowledge, relative to production knowledge, as the key constraint to achieve consistent export to developed countries.